Mapping Research Trends on Illegal Abortion Behavior: A Bibliometric Study - Kusnali, Asep; Puspasari, Herti Windya; Mustikawati, Intan Silviana (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
Research on the topic of illegal abortion is quite a concern, but more discussed macro in a legal point of view and health policy. Micro-analysis with a similar topic has been conducted on a limited basis with the background of the issue of illegality which cannot prevent abortion behavior. This study aims to analyze the scientific literature to find general trends and analyze indicators related to the topic of behavior from illegal abortion practices around the world. This paper uses a bibliometric methodology, utilizing data taken from the Scopus database from 1968 to 2021, and visualizing the data using the VOSviewer. 310 papers from different nations were uncovered in the investigation. When the study's findings are compared to the total number of citations and related publications, it becomes clear that the United States and the United Kingdom continue to dominate research on illegal abortion activity. The great majority of articles on this topic are mostly in the social science sector. By identifying keywords, it can be seen that the majority of research topics continue to center on large-scale issues including abortion, contraception, and unsafe abortion. This study enables us to define unlawful abortion in an individual setting as the behavior a person engages in when deciding to abort a pregnancy, regardless of whether it is carried out by themself, another person, medical professional, health workers, health facilities, or by other parties that deviate from the abortion laws that are in effect in the nation. This study offers crucial conclusions and suggestions for future thematic research opportunities that are sustainable.